Sodium electric quaternary precursor and preparation method and application thereof

By preparing the sodium-electric quaternary precursor NixCuyTizMn1-x-y-z(CO3)1+z, the complexation and co-precipitation technology of nickel, copper, manganese and titanium ions was solved, and the problem of loose and insufficient stability of sodium-electric positive electrode material was solved. It achieves high tap density and excellent air and circulation stability, and improves the performance of sodium ion batteries.

CN119284985APending Publication Date: 2025-01-10HUAYOU NEW ENERGY TECH (QUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411203271.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The electrode material design of sodium ion batteries faces the problems of loose particles, poor spherical formation, wide particle distribution and low tap density. In particular, Ti elements are difficult to co-precipitate with other metal elements, resulting in air stability and circulation of sodium oxidized electrode materials. Inadequate stability.

Method used

Using the sodium-electric quaternary precursor NixCuyTizMn1-x-y-z(CO3)1+z, a uniform metal liquid was formed through the complexing reaction of nickel, copper, manganese, titanium ions and complexing agent, and Cu and The sodium-electric quaternary precursor with uniform distribution of Ti elements improves the tap density and stability of the positive electrode material.

Benefits of technology

The high tap density, excellent air stability and circulation stability of sodium-electric quadron cathode material are achieved, and the battery packing capacity and high-temperature circulation performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284985A_ABST
    Figure CN119284985A_ABST
Patent Text Reader

Abstract

The invention relates to a sodium electric quaternary precursor and a preparation method and application thereof, the molecular formula of the sodium electric quaternary precursor is NixCuyTizMn1-x-y-z (CO3) 1 + z, 0 < x < 1, 0 < y < 1, 0 < z < 1, x + y + z < 1, the absolute value of the difference between y and z is less than or equal to 0.2, the sodium electric quaternary precursor comprises secondary particles formed by primary particles, the primary particles are in a sheet shape, the thickness is 10-200 nm, and the thickness of the primary particles is 10-200 nm. The tap density of the sodium electric quaternary precursor is greater than or equal to 0.5 g / cm < 3 >. The sodium-electric quaternary precursor is high in tap density and is doped with the Cu element and the Ti element, the Cu element and the Ti element are similar in doping amount and uniform in distribution, and when the sodium-electric quaternary precursor is used for preparing the sodium-electric quaternary positive electrode material, the prepared sodium-electric quaternary positive electrode material has excellent air stability and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium batteries, and in particular to a sodium battery quaternary precursor and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have the characteristics of abundant raw materials, low cost, safety, and high energy efficiency, providing a feasible solution for large-scale energy storage systems. + / Na's standard potential (-2.73Vvs. standard hydrogen electrode) is higher than Li + The standard potential of / Li (-3.02V vs. standard hydrogen electrode) reduces the potential for normal operation of the battery, restricting the energy / power density of the sodium ion battery. + The large ionic radius of Na + The slow kinetics poses a great challenge to the design of electrode materials for sodium-ion batteries, especially the sodium cathode materials that determine the basic properties of sodium-ion batteries.

[0003] Sodium battery cathode materials are prepared from precursors through solid phase sintering. The addition of doping elements can further improve the performance of sodium battery cathode materials. For example, the Cu element can increase the voltage platform and improve the air stability, and the Ti element can improve the cycle stability of the sodium battery cathode material. However, since Ti is very easy to precipitate and cannot be co-precipitated with other metal elements, the prepared precursor has problems such as loose particles, poor sphericity, extremely wide particle distribution, empty stacking, and low tap density. Summary of the invention

[0004] Based on this, it is necessary to provide a sodium-ion battery quaternary precursor and a preparation method and application thereof to address the above-mentioned problems. The sodium-ion battery quaternary precursor has a high tap density and is doped with Cu and Ti elements at the same time, and the doping amounts of Cu and Ti elements are similar and uniformly distributed. When the sodium-ion battery quaternary precursor is used to prepare a sodium-ion battery quaternary positive electrode material, the obtained sodium-ion battery quaternary positive electrode material has excellent air stability and cycle stability.

[0005] The invention discloses a sodium quaternary precursor, wherein the molecular formula of the sodium quaternary precursor is Ni x Cu y Ti z Mn 1-x-y-z (CO3) 1+z , wherein 0<x<1, 0<y<1, 0<z<1, x+y+z<1, the absolute value of the difference between y and z is less than or equal to 0.2, the sodium quaternary precursor comprises secondary particles formed by primary particles, the primary particles are in the form of flakes, and the thickness is 10nm-200nm, and the tap density of the sodium quaternary precursor is greater than or equal to 0.5g / cm3 .

[0006] In one embodiment, in the molecular formula of the sodium quaternary precursor, 0.01≤x≤0.8,

[0007] 0.01≤y≤0.8, 0.01≤z≤0.8.

[0008] In one embodiment, the sodium quaternary precursor satisfies at least one of the following conditions:

[0009] (1) The secondary particles are spherical and have a particle size of 3 μm-10 μm;

[0010] (2) The particle size distribution coefficient K of the sodium quaternary precursor 90 0.6-0.9;

[0011] (3) The tap density of the sodium quaternary precursor is 0.5 g / cm 3 -1.6g / cm 3 ;

[0012] (4) The specific surface area of ​​the sodium quaternary precursor is 10.0 m 2 / g-40.0m 2 / g.

[0013] The sodium quaternary precursor provided by the present invention is doped with Cu and Ti at the same time, and the doping amounts are similar. The Cu and Ti elements are evenly distributed in the sodium quaternary precursor, and there is no concentration gradient or segregation. At the same time, the primary particles of the sodium quaternary precursor are in the form of thin sheets with a specific thickness, and the tap density of the sodium quaternary precursor is greater than or equal to 0.5 g / cm 3 When the sodium-ion battery quaternary precursor is used to prepare the sodium-ion battery quaternary positive electrode material, the filling amount can be increased. In addition, since the sodium-ion battery quaternary positive electrode material has good inheritance of the tap density and element distribution of the sodium-ion battery quaternary precursor, the prepared sodium-ion battery quaternary positive electrode material has a high tap density, and the Cu and Ti elements are evenly distributed, there is no concentration gradient, and there is no segregation. The prepared sodium-ion battery quaternary positive electrode material has excellent air stability and cycle stability.

[0014] A method for preparing the sodium quaternary precursor as described above comprises the following steps:

[0015] A nickel salt, a copper salt, a manganese salt and a first complexing agent are mixed to carry out a complexing reaction to obtain a first metal liquid, and a titanium salt and a second complexing agent are mixed to carry out a complexing reaction to obtain a second metal liquid, wherein the stability constant of the complexing of the first complexing agent with the copper salt is 10-18, and the stability constant of the complexing of the second complexing agent with the titanium salt is 2-10; and

[0016] The first metal liquid, the second metal liquid and the precipitant are added to the bottom liquid at the same time to perform a co-precipitation reaction. 50 After the particle size reaches the target size, the reaction is completed to obtain the sodium quaternary precursor; wherein the base liquid is alkaline, the precipitant includes at least one of sodium bicarbonate, sodium carbonate or ammonium bicarbonate, and the concentration of copper ions in the first metal liquid is c a , the concentration of titanium ions in the second metal liquid is c b , c a With c b The absolute value of the difference is less than or equal to 0.5 mol / L, and the addition rate of the first metal liquid is v a , the addition rate of the second metal liquid is v b ,|v a -v b | represents v a With v b The absolute value of the difference, |v a -v b The ratio of the volume of the base liquid is less than or equal to 0.02h -1 .

[0017] In one embodiment, the first complexing agent includes at least one of ammonium citrate, glycine, sodium citrate, tartaric acid, citric acid, acetic acid or stearic acid;

[0018] And / or, the second complexing agent includes at least one of ethylenediaminetetraacetic acid, triethanolamine, disodium ethylenediaminetetraacetate, ethanolamine or hydrogen peroxide.

[0019] In one embodiment, the step of mixing the nickel salt, the copper salt, the manganese salt and the first complexing agent to perform a complexing reaction to obtain the first metal liquid satisfies at least one of the following conditions:

[0020] (1) The total concentration of nickel ions, copper ions and manganese ions in the first metal liquid is 0.1 mol / L-3 mol / L, and the concentration of copper ions is c a Between 0.05mol / L-1.0mol / L;

[0021] (2) In the first metal liquid, the concentration of the first complexing agent is 2 g / L-10 g / L.

[0022] In one embodiment, the step of mixing the titanium salt and the second complexing agent for complexing reaction satisfies at least one of the following conditions:

[0023] (1) The concentration of titanium ions in the second metal liquid is c b Between 0.05mol / L-1.2mol / L;

[0024] (2) In the second metal liquid, the concentration of the second complexing agent is 0.5 g / L-3 g / L.

[0025] In one embodiment, the step of simultaneously adding the first metal liquid, the second metal liquid and the precipitant into the bottom liquid for co-precipitation reaction satisfies at least one of the following conditions:

[0026] (1) The base liquid includes a third complexing agent and an alkaline compound, wherein the pH of the base liquid is greater than 7 and less than 11, the third complexing agent includes at least one of ammonium citrate, glycine, sodium citrate, tartaric acid, citric acid, acetic acid or stearic acid, and the alkaline compound includes at least one of sodium carbonate, ammonium bicarbonate or sodium bicarbonate;

[0027] (2) The temperature of the base liquid is 40°C-70°C;

[0028] (3) Based on 200 L of the base liquid, the addition rate of the first metal liquid is v a The addition rate of the second metal liquid v is between 1.2 L / h and 6.0 L / h. b Between 1.0L / h-6.4L / h;

[0029] (4) Based on 200 L of the bottom liquid, the addition rate of the precipitant is v c , v c Between 3.0L / h-10.0L / h;

[0030] (5) The step of performing the coprecipitation reaction is carried out under stirring conditions, and the stirring speed is 100 rpm-800 rpm.

[0031] In the preparation method of the sodium quaternary precursor provided by the present invention, firstly, nickel, copper and manganese salts are complexed with a first complexing agent, and titanium salts are complexed with a second complexing agent, so that nickel, copper, manganese ions and titanium ions are uniformly and stably dispersed in a first metal liquid and a second metal liquid respectively, and uniform complexation at the atomic level is achieved, thereby reducing the difference in precipitation speed of each metal ion in a subsequent coprecipitation reaction process; secondly, at least one of sodium bicarbonate, sodium carbonate or ammonium bicarbonate is used as a precipitant, and the precipitant has a similar precipitation ability to nickel, copper, manganese ions and titanium ions; thirdly, the first metal liquid, the second metal liquid and the precipitant are simultaneously added to the bottom liquid for a coprecipitation reaction, and the |v a -v b |The ratio of the volume of the base liquid is less than or equal to 0.02h -1 , and finally achieve uniform co-precipitation, so that the Cu element and the Ti element are evenly distributed in the sodium-ion battery precursor, and the prepared sodium-ion battery precursor has a high tap density.

[0032] A sodium-ion battery quaternary positive electrode material prepared using the sodium-ion battery quaternary precursor as described above.

[0033] A method for preparing the sodium quaternary positive electrode material as described above comprises the following steps:

[0034] Providing a sodium quaternary precursor as described above; and

[0035] The sodium-based quaternary precursor is mixed with a sodium source in proportion and solid-phase sintered to obtain a sodium-based quaternary positive electrode material.

[0036] The preparation method of the sodium quaternary positive electrode material provided by the present invention uses the above-mentioned sodium quaternary positive electrode precursor as a raw material. Since the sodium quaternary positive electrode material has good inheritance of the tap density and element distribution of the sodium quaternary positive electrode precursor, the prepared sodium quaternary positive electrode material has high tap density, excellent air stability and cycle stability.

[0037] A positive electrode sheet is prepared using the sodium quaternary positive electrode material as mentioned above.

[0038] A sodium ion battery comprises the positive electrode sheet as described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 This is a scanning electron microscope image of the sodium quaternary precursor prepared in Example 1;

[0041] Figure 2 This is a scanning electron microscope image of the sodium quaternary precursor prepared in Comparative Example 1;

[0042] Figure 3 This is a scanning electron microscope image of the sodium quaternary precursor prepared in Comparative Example 2;

[0043] Figure 4 This is a scanning electron microscope image of the sodium quaternary precursor prepared in Comparative Example 3;

[0044] Figure 5 This is a scanning electron microscope image of the sodium quaternary precursor prepared in Comparative Example 4;

[0045] Figure 6 This is a scanning electron microscope image of the sodium quaternary precursor prepared in Example 7;

[0046] Figure 7 This is a scanning electron microscope image of the sodium quaternary precursor prepared in Example 8;

[0047] Figure 8 This is a scanning electron microscope image of the sodium quaternary precursor prepared in Example 9;

[0048] Fig. 9 This is a scanning electron microscope image of the sodium quaternary precursor prepared in Example 10. DETAILED DESCRIPTION

[0049] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the technical field of the terminology of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.

[0051] In a first aspect of the present invention, a sodium quaternary precursor is provided, wherein the molecular formula of the sodium quaternary precursor is Ni x Cu y Ti z Mn 1-x-y-z (CO3) 1+z , wherein 0<x<1, 0<y<1, 0<z<1, x+y+z<1, the absolute value of the difference between y and z is less than or equal to 0.2, the sodium quaternary precursor comprises secondary particles formed by primary particles, the primary particles are in the form of flakes, and the thickness is 10nm-200nm, and the tap density of the sodium quaternary precursor is greater than or equal to 0.5g / cm 3 .

[0052] The sodium quaternary precursor provided by the present invention is doped with Cu and Ti at the same time, and the doping amounts are similar. The Cu and Ti elements are evenly distributed in the sodium quaternary precursor, and there is no concentration gradient or segregation. At the same time, the primary particles of the sodium quaternary precursor are in the form of thin sheets with a specific thickness, and the tap density of the sodium quaternary precursor is greater than or equal to 0.5 g / cm 3 .

[0053] When the sodium-ion quaternary precursor is used to prepare the sodium-ion quaternary positive electrode material, the filling amount can be increased. In addition, since the sodium-ion quaternary positive electrode material has good inheritance of the tap density and element distribution of the sodium-ion quaternary precursor, the prepared sodium-ion quaternary positive electrode material has a high tap density, and the Cu and Ti elements are evenly distributed, there is no concentration gradient, and there is no segregation. The prepared sodium-ion quaternary positive electrode material has excellent air stability and cycle stability.

[0054] Including but not limited to, the thickness of the primary particle is 10nm-200nm, including but not limited to 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm or 200nm.

[0055] In one embodiment, in the molecular formula of the sodium quaternary precursor, 0.01≤x≤0.8, 0.01≤y≤0.8, 0.01≤z≤0.8, including but not limited to, x is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, y is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, and z is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8.

[0056] In one embodiment, the secondary particles are spherical and have a particle size of 3 μm-10 μm, including but not limited to 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0057] In one embodiment, the particle size distribution of the sodium quaternary precursor is relatively narrow, and the particle size distribution coefficient K 90 is 0.6-0.9, including but not limited to 0.6, 0.7, 0.8 or 0.9; it can be understood that K 90 The closer the value is to 1, the more uniform the particle distribution is.

[0058] It can be understood that since the sodium quaternary positive electrode material has good inheritance in terms of the tap density, particle size and morphology of the sodium quaternary precursor, in order to increase the volume energy density of the battery by increasing the tap density of the sodium quaternary precursor, in one embodiment, the tap density of the sodium quaternary precursor is 0.5 g / cm 3 -1.6g / cm 3 , including but not limited to 0.5g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3, 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 or 1.6 g / cm 3 .

[0059] The specific surface area of ​​the sodium quaternary precursor affects the microstructure and morphology of the sodium quaternary cathode material. In one embodiment, the specific surface area of ​​the sodium quaternary precursor is 10.0 m 2 / g-40.0m 2 / g, including but not limited to 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g or 40m 2 / g.

[0060] The second aspect of the present invention provides a method for preparing the sodium quaternary precursor as described above, comprising the following steps:

[0061] S101, mixing a nickel salt, a copper salt, a manganese salt and a first complexing agent for complexing reaction to obtain a first metal liquid, and performing a complexing reaction on a titanium salt and a second complexing agent to obtain a second metal liquid; and

[0062] S102, adding the first metal liquid, the second metal liquid and the precipitant into the bottom liquid at the same time to perform a co-precipitation reaction, when the product D 50 After the particle size reaches the target size, the reaction is completed and a sodium quaternary precursor is obtained; wherein the base liquid is alkaline, the precipitant includes at least one of sodium bicarbonate, sodium carbonate or ammonium bicarbonate, and the concentration of copper ions in the first metal liquid is c a , the concentration of titanium ions in the second metal liquid is c b , c a With c b The absolute value of the difference is less than or equal to 0.5 mol / L, and the addition rate of the first metal liquid is v a , the addition rate of the second metal liquid is v b ,|v a -v b | represents v a With v b The absolute value of the difference, |v a -v b|The ratio of the volume of the base liquid is less than or equal to 0.02h -1 .

[0063] In step S101, nickel, copper, and manganese salts are complexed with the first complexing agent, and titanium salts are complexed with the second complexing agent, so that nickel, copper, manganese ions, and titanium ions are uniformly and stably dispersed in the first metal liquid and the second metal liquid, respectively, to achieve uniform complexation at the atomic level, thereby reducing the difference in precipitation rates of each metal ion in the subsequent co-precipitation reaction process.

[0064] In the first metal liquid, the stability constant of the complexation between the first complexing agent and the copper salt is 10-18, including but not limited to 10, 11, 12, 13, 14, 15, 16, 17 or 18. In one embodiment, the first complexing agent includes at least one of ammonium citrate, glycine, sodium citrate, tartaric acid, citric acid, acetic acid or stearic acid.

[0065] The concentration of the first complexing agent affects the electron microscopic morphology and tap density of the sodium-ion battery precursor. In one embodiment, in the first metal liquid, the concentration of the first complexing agent is 2g / L-10g / L, including but not limited to 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L or 10g / L.

[0066] In one embodiment, the nickel salt comprises at least one of nickel sulfate, nickel chloride, nickel nitrate or nickel acetate, preferably nickel sulfate; the copper salt comprises at least one of copper sulfate, copper chloride, copper nitrate or copper acetate, preferably copper sulfate; the cobalt salt comprises at least one of cobalt sulfate, cobalt chloride, cobalt nitrate or cobalt acetate, preferably cobalt sulfate.

[0067] By controlling the molar ratio of nickel ions, copper ions and manganese ions, sodium quaternary precursors with different proportions can be prepared. In one embodiment, the molar ratio of nickel ions, copper ions and manganese ions in the metal salt solution is 4:1:4, 3:1:5, 5:1:3, 6:1:2, and 2:1:6.

[0068] By controlling the total concentration of metal ions in the metal salt solution, the growth rate of the sodium quaternary precursor can be controlled. In one embodiment, the total concentration of nickel ions, copper ions and manganese ions in the first metal liquid is 0.1 mol / L-3 mol / L, including but not limited to 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L or 0.3 mol / L.

[0069] In one embodiment, the concentration of copper ions c aBetween 0.05mol / L-1.0mol / L; including but not limited to 0.05mol / L, 0.15mol / L, 0.25mol / L, 0.35mol / L, 0.45mol / L, 0.55mol / L, 0.65mol / L, 0.75mol / L, 0.85mol / L, 0.95mol / L or 1.0mol / L.

[0070] In the second metal liquid, the stability constant of the second complexing agent and the titanium salt complex is 2-10, including but not limited to 2, 3, 4, 5, 6, 7, 8, 9 or 10. In one embodiment, the second complexing agent includes at least one of ethylenediaminetetraacetic acid, triethanolamine, disodium ethylenediaminetetraacetate, ethanolamine or hydrogen peroxide.

[0071] The concentration of the second complexing agent affects the proportion of titanium ions. In one embodiment, in the second metal liquid, the concentration of the second complexing agent is 0.5 g / L-3 g / L, including but not limited to 0.5 g / L, 1.0 g / L, 1.5 g / L, 2.0 g / L, 2.5 g / L or 3.0 g / L.

[0072] In one embodiment, the titanium salt comprises at least one of titanium sulfate or titanyl sulfate, preferably titanium sulfate.

[0073] In one embodiment, the concentration of titanium ions in the second metal liquid is c b Between 0.05mol / L-1.2mol / L; including but not limited to 0.05mol / L, 0.15mol / L, 0.25mol / L, 0.35mol / L, 0.45mol / L, 0.55mol / L, 0.65mol / L, 0.75mol / L, 0.85mol / L, 0.95mol / L, 1.05mol / L, 1.15mol / L or 1.2mol / L.

[0074] In step S102, sodium bicarbonate, sodium carbonate or ammonium bicarbonate is used as a precipitant, which has similar precipitation ability with nickel, copper, manganese ions and titanium ions to avoid precipitation segregation; at the same time, the first metal liquid, the second metal liquid and the precipitant are added to the bottom liquid for co-precipitation reaction, and the |v a -v b |The ratio of the volume of the base liquid is less than or equal to 0.02h -1 , including but not limited to 0h -1 , 0.005h -1 , 0.01h -1 、0.015h -1 or 0.02h -1, and finally achieve uniform co-precipitation, so that the Cu element and the Ti element are evenly distributed in the sodium-ion battery precursor, and the obtained sodium-ion battery precursor has a high tap density. In addition, the uniform co-precipitation can also make the obtained sodium-ion battery precursor have excellent sphericity, formability, and uniformity.

[0075] The pH of the base liquid affects the size and growth rate of primary particles in the coprecipitation reaction system. Stable primary particles can ensure a more uniform secondary ball agglomeration effect, thereby preparing a sodium-ion battery precursor with good sphericity and uniformity. In one embodiment, the pH of the base liquid is greater than 7 and less than 11. Specifically, the pH of the base liquid is 7.5, 8, 8.5, 9, 9.5, 10 or 10.5.

[0076] In addition, the pH and temperature of the base liquid also affect the specific surface area of ​​the prepared sodium-ion battery precursor. In one embodiment, the temperature of the base liquid is 40°C-70°C, including but not limited to 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C.

[0077] In one embodiment, the base liquid includes a third complexing agent and an alkaline compound; the third complexing agent is preferably at least one of ammonium citrate, glycine, sodium citrate, tartaric acid, citric acid, acetic acid or stearic acid, and the alkaline compound preferably includes at least one of sodium carbonate, sodium bicarbonate or ammonium bicarbonate.

[0078] In one embodiment, the addition rate v of the first molten metal is a The addition rate of the second metal liquid is between 1.2 L / h and 6.0 L / h, including but not limited to 1.2 L / h, 2.0 L / h, 3.0 L / h, 4.0 L / h, 5.0 L / h or 6.0 L / h. b Between 1.0 L / h-6.4 L / h, including but not limited to 1.0 L / h, 2.0 L / h, 3.0 L / h, 4.0 L / h, 5.0 L / h, 6.0 L / h or 6.4 L / h.

[0079] In one embodiment, the coprecipitation reaction is carried out under stirring conditions. Stirring can increase the shear force of the fluid, prevent the particles from sticking and growing in clusters, and accelerate the diffusion of solute ions to prevent the occurrence of local high supersaturation, thereby obtaining seed particles with more uniform particle size and better dispersion. Preferably, in the step of carrying out the coprecipitation reaction, the stirring speed is 100rpm-800rpm, including but not limited to 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm or 800rpm.

[0080] In one embodiment, after the coprecipitation reaction, the obtained sodium quaternary precursor is centrifuged and washed with 0.8 mol / L-8 mol / L alkali solution at 5 rpm-20 rpm for 8 min-12 min, and then centrifuged and washed with water at 5 rpm-20 rpm for 8 min-12 min; the washed sodium quaternary precursor is dried at 60°C-150°C for 10h-40h.

[0081] The third aspect of the present invention provides a sodium quaternary cathode material prepared using the sodium quaternary precursor as described above.

[0082] Since the sodium-ion battery quaternary positive electrode material provided by the present invention has excellent high tap density, excellent air stability and cycle stability, after the sodium-ion battery quaternary positive electrode material is assembled into a sodium-ion battery, the sodium-ion battery has excellent capacity and high-temperature cycle performance.

[0083] A fourth aspect of the present invention provides a method for preparing the sodium quaternary cathode material as described above, comprising the following steps:

[0084] S201, providing the sodium quaternary precursor as described above; and

[0085] S202, mixing the sodium quaternary precursor and the sodium source in proportion, and performing solid phase sintering to obtain the sodium quaternary positive electrode material.

[0086] In one embodiment, the sintering temperature is 400°C-700°C, including but not limited to 400°C, 500°C, 600°C or 700°C.

[0087] In one embodiment, in the step of performing solid phase sintering, the sintering time is 3h-8h, including but not limited to 3h, 4h, 5h, 6h, 7h or 8h.

[0088] The preparation method of the sodium quaternary positive electrode material provided by the present invention is based on the above-mentioned sodium quaternary positive electrode precursor. Since the sodium quaternary positive electrode material has good inheritance of the tap density and element distribution of the sodium quaternary positive electrode precursor, the prepared quaternary positive electrode material has high tap density, excellent air stability and cycle stability.

[0089] A fifth aspect of the present invention provides a positive electrode sheet, which is prepared using the sodium quaternary positive electrode material as described above.

[0090] A sixth aspect of the present invention provides a sodium ion battery comprising the positive electrode sheet as described above.

[0091] Hereinafter, the sodium quaternary precursor and its preparation method and application will be further described through the following specific examples.

[0092] Example 1

[0093] Nickel sulfate, copper sulfate and manganese sulfate are first complexed with sodium citrate in a molar ratio of 4:1:4, and then mixed with pure water to form a first metal liquid. In the first metal liquid, the total concentration of nickel ions, copper ions and manganese ions is 1.665 mol / L, and the concentration of sodium citrate is 3 g / L.

[0094] Titanium sulfate and EDTA are first complexed at a molar ratio of 1:1, and then mixed with pure water to prepare a second metal liquid. In the second metal liquid, the concentration of titanium ions is 0.185 mol / L, and the concentration of EDTA is 2 g / L.

[0095] A certain amount of pure water was injected into the reactor, nitrogen was blown in, the reactor stirrer was turned on, the stirring speed was between 400rpm-600rpm, the temperature was raised to 50°C, sodium citrate and 1.67mol / L sodium carbonate solution were added into the reactor to obtain a bottom liquid, in which the concentration of sodium citrate was 3g / L, and the pH of the bottom liquid was alkaline, the first metal liquid, the second metal liquid and 1.67mol / L sodium carbonate solution were simultaneously added into the bottom liquid for coprecipitation reaction, wherein the flow rate of the first metal liquid was 4.0L / h, the flow rate of the second metal liquid was 4.0L / h, the flow rate of the sodium carbonate solution was 7.0L / h, the pH of the liquid in the reactor was 7.8, the feed was continuously added to clear and concentrate, and the particle size reached 5μm, the feed was stopped, the material was filtered to obtain the material, the material was sequentially washed and oven dried to obtain TD>1.0g / cm 3 Ni with a particle size of 5 μm 0.4 Cu 0.1 Ti 0.1 Mn 0.4 (CO3) 1.1 The SEM image of the sodium quaternary precursor is shown in Figure 2. Figure 1 As shown by Figure 1 It can be seen that the sodium-ion battery precursor contains secondary particles formed by primary particles, the primary particles are in the form of flakes, and the secondary particles are in the form of spheres.

[0096] The prepared sodium quaternary precursor Ni 0.4 Cu 0.1 Ti 0.1 Mn 0.4 (CO3) 1.1 and sodium carbonate in a molar ratio of Na:(Ni 0.4 Cu 0.1 Ti 0.1 Mn 0.4 )=1.05:1 ratio for dry mixing, and then the mixture is subjected to solid phase sintering reaction in a pure oxygen atmosphere, the solid phase sintering reaction temperature is 900° C., the reaction time is 12 h, and a sodium battery quaternary positive electrode material is obtained.

[0097] Comparative Example 1

[0098] Comparative Example 1 was carried out in accordance with Example 1, except that sodium citrate was replaced by ammonia water, and EDTA was replaced by ethylenediamine; the scanning electron microscope image of the prepared sodium quaternary precursor is as follows: Figure 2 shown.

[0099] Comparative Example 2

[0100] Comparative Example 2 was carried out with reference to Example 1, except that the sodium carbonate solution was replaced with a sodium hydroxide solution. The scanning electron microscope image of the prepared sodium quaternary precursor is as follows: Figure 3 shown.

[0101] Comparative Example 3

[0102] The method is carried out in accordance with Example 1, except that nickel ions, copper ions, manganese ions and titanium ions are mixed with sodium citrate as the metal liquid. The scanning electron microscope image of the prepared sodium quaternary precursor is as follows: Figure 4 shown.

[0103] Comparative Example 4

[0104] The method was carried out in accordance with Example 1, except that nickel ions, copper ions, manganese ions and titanium ions were mixed with EDTA as the metal liquid. The scanning electron microscope image of the prepared sodium quaternary precursor is as follows: Figure 5 shown.

[0105] Test Example 1

[0106] The particle size, K 90 , tap density (TD), specific surface area (SSA) and thickness of primary particles. The specific test methods are as follows, and the test results are shown in Table 1; The air stability, cycle stability and electrochemical properties of the sodium-ion battery quaternary positive electrode materials prepared in Test Example 1 and Comparative Examples 1-4 are as follows, and the specific test methods are as follows, and the test results are shown in Table 2.

[0107] Particle size: The particle size distribution of the sodium electrolyte precursor was determined by laser diffraction.

[0108] K 90 :Determination of D of Sodium Electron Precursors by Laser Diffraction 90 , D 10 and D 50 , according to K 90 =(D 90 -D 10 ) / D 50 Calculate K 90 .

[0109] Tap density (TD): The sodium quaternary precursor in the container is tapped and the mass per unit volume is measured.

[0110] Specific surface area (SSA): measured by low temperature nitrogen adsorption method.

[0111] Air stability: Use a carbon-sulfur analyzer to test the carbon content in air at 25°C and 40RH% for 48 hours.

[0112] Cycle stability: Use a blue power tester to perform charge and discharge tests in the voltage range of 2.5-4.1V, and test the capacity retention rate after 50 cycles at 1C.

[0113] Capacity of deducted electricity: Use a blue electricity tester to perform charge and discharge tests between the voltage range of 2.5-4.1V, and test the 0.1C first cycle charge and discharge capacity.

[0114] Table 1

[0115]

[0116] Table 2

[0117]

[0118] Example 2

[0119] Example 2 was carried out with reference to Example 1, except that EDTA was replaced by H2O2.

[0120] Example 3

[0121] Example 3 was carried out with reference to Example 1, except that sodium citrate was replaced by citric acid.

[0122] Example 4

[0123] Example 4 was carried out with reference to Example 1, except that sodium citrate was replaced by citric acid, and EDTA was replaced by H2O2.

[0124] Example 5

[0125] Example 5 was carried out with reference to Example 1, except that sodium citrate was replaced by acetic acid.

[0126] Example 6

[0127] Example 6 was carried out with reference to Example 1, except that sodium citrate was replaced by acetic acid, and EDTA was replaced by H2O2.

[0128] Example 7

[0129] Example 7 is carried out in accordance with Example 1, except that the concentration of sodium citrate in the first metal liquid is 0.5 g / L; the concentration of EDTA in the second metal liquid is 0.5 g / L; the scanning electron microscope image of the obtained sodium quaternary precursor is as follows: Figure 6 shown.

[0130] Example 8

[0131] Example 8 was carried out with reference to Example 1, except that the flow rate of the sodium carbonate solution was 12 L / h; the scanning electron microscope image of the obtained sodium quaternary precursor is as follows: Figure 7 shown.

[0132] Example 9

[0133] Example 9 was carried out with reference to Example 1, except that in the step of coprecipitation reaction, the stirring speed was 300 rpm; the scanning electron microscope image of the obtained sodium quaternary precursor is as follows: Figure 8 shown.

[0134] Example 10

[0135] Example 10 was carried out in accordance with Example 1, except that the pH of the base liquid was 10, and in the step of coprecipitation reaction, the pH of the liquid in the reactor was 10; the scanning electron microscope image of the obtained sodium quaternary precursor is as follows: Fig. 9 shown.

[0136] Test Example 2

[0137] Referring to Test Example 1, the particle size, K 90 , tap density (TD), specific surface area (SSA), and the test results are shown in Table 3; the air stability, cycle stability and electrochemical properties of the sodium-ion battery quaternary positive electrode materials prepared in Example 2-10 were tested, and the test results are shown in Table 4.

[0138] Table 3

[0139]

[0140] Table 4

[0141]

[0142] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0143] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A sodium quaternary precursor, characterized in that: The molecular formula of the sodium quaternary precursor is Ni x Cu y Ti z Mn 1-x-y-z (CO3) 1+z , wherein 0<x<1, 0<y<1, 0<z<1, x+y+z<1, the absolute value of the difference between y and z is less than or equal to 0.2, the sodium quaternary precursor comprises secondary particles formed by primary particles, the primary particles are in the form of flakes, and the thickness is 10nm-200nm, and the tap density of the sodium quaternary precursor is greater than or equal to 0.5g / cm 3 .

2. The sodium quaternary precursor according to claim 1, characterized in that: In the molecular formula of the sodium quaternary precursor, 0.01≤x≤0.8, 0.01≤y≤0.8, 0.01≤z≤0.

8.

3. The sodium quaternary precursor according to claim 1, characterized in that: The sodium quaternary precursor satisfies at least one of the following conditions: (1) The secondary particles are spherical and have a particle size of 3 μm-10 μm; (2) The particle size distribution coefficient K of the sodium quaternary precursor 90 0.6-0.9; (3) The tap density of the sodium quaternary precursor is 0.5 g / cm 3 -1.6g / cm 3 ; (4) The specific surface area of ​​the sodium quaternary precursor is 10.0 m 2 / g-40.0m 2 / g.

4. A method for preparing a sodium quaternary precursor according to any one of claims 1 to 3, characterized in that: The following steps are involved: A nickel salt, a copper salt, a manganese salt and a first complexing agent are mixed to carry out a complexing reaction to obtain a first metal liquid, and a titanium salt and a second complexing agent are mixed to carry out a complexing reaction to obtain a second metal liquid, wherein the stability constant of the complexing of the first complexing agent with the copper salt is 10-18, and the stability constant of the complexing of the second complexing agent with the titanium salt is 2-10; and The first metal liquid, the second metal liquid and the precipitant are added to the bottom liquid at the same time to perform a co-precipitation reaction. 50 After the particle size reaches the target size, the reaction is completed to obtain the sodium quaternary precursor; wherein the base liquid is alkaline, the precipitant includes at least one of sodium bicarbonate, sodium carbonate or ammonium bicarbonate, and the concentration of copper ions in the first metal liquid is c a , the concentration of titanium ions in the second metal liquid is c b , c a With c b The absolute value of the difference is less than or equal to 0.5 mol / L, and the addition rate of the first metal liquid is v a , the addition rate of the second metal liquid is v b ,|v a -v b | represents v a With v b The absolute value of the difference, |v a -v b The ratio of the volume of the base liquid is less than or equal to 0.02h -1 .

5. The method for preparing a sodium quaternary precursor according to claim 4, characterized in that: The first complexing agent includes at least one of ammonium citrate, glycine, sodium citrate, tartaric acid, citric acid, acetic acid or stearic acid; And / or, the second complexing agent includes at least one of ethylenediaminetetraacetic acid, triethanolamine, disodium ethylenediaminetetraacetate, ethanolamine or hydrogen peroxide.

6. The method for preparing a sodium quaternary precursor according to claim 4, characterized in that: The step of mixing the nickel salt, the copper salt, the manganese salt and the first complexing agent to perform a complexing reaction to obtain the first metal liquid satisfies at least one of the following conditions: (1) The total concentration of nickel ions, copper ions and manganese ions in the first metal liquid is 0.1 mol / L-3 mol / L, and the concentration of copper ions is c a Between 0.05mol / L-1.0mol / L; (2) In the first metal liquid, the concentration of the first complexing agent is 2 g / L-10 g / L.

7. The method for preparing a sodium quaternary precursor according to claim 4, characterized in that: The step of mixing the titanium salt and the second complexing agent for complexing reaction satisfies at least one of the following conditions: (1) The concentration of titanium ions in the second metal liquid is c b Between 0.05mol / L-1.2mol / L; (2) In the second metal liquid, the concentration of the second complexing agent is 0.5 g / L-3 g / L.

8. The method for preparing a sodium quaternary precursor according to claim 4, characterized in that: The step of simultaneously adding the first metal liquid, the second metal liquid and the precipitant into the bottom liquid for co-precipitation reaction satisfies at least one of the following conditions: (1) The base liquid includes a third complexing agent and an alkaline compound, wherein the pH of the base liquid is greater than 7 and less than 11, the third complexing agent includes at least one of ammonium citrate, glycine, sodium citrate, tartaric acid, citric acid, acetic acid or stearic acid, and the alkaline compound includes at least one of sodium carbonate, ammonium bicarbonate or sodium bicarbonate; (2) The temperature of the base liquid is 40°C-70°C; (3) Based on 200 L of the base liquid, the addition rate of the first metal liquid is v a The addition rate of the second metal liquid v is between 1.2 L / h and 6.0 L / h. b Between 1.0L / h-6.4L / h; (4) Based on 200 L of the bottom liquid, the addition rate of the precipitant is v c , v c Between 3.0L / h-10.0L / h; (5) The step of performing the coprecipitation reaction is carried out under stirring conditions, and the stirring speed is 100 rpm-800 rpm.

9. A sodium quaternary positive electrode material prepared using the sodium quaternary precursor as described in any one of claims 1 to 3.

10. A method for preparing the sodium quaternary positive electrode material according to claim 9, characterized in that: The following steps are involved: Providing a sodium quaternary precursor as described in any one of claims 1 to 3; and The sodium-based quaternary precursor is mixed with a sodium source in proportion and solid-phase sintered to obtain a sodium-based quaternary positive electrode material.

11. A positive electrode sheet prepared using the sodium quaternary positive electrode material as claimed in claim 9.

12. A sodium ion battery comprising the positive electrode sheet according to claim 11.